IMPROVEMENT OF METHODS OF CONSERVATIVE THERAPY OF EXUDATIVE OTITIS MEDIA IN CHILDREN - Erkinovich, Shadiev Anvar; O’g’li, Akramov Shamsiddin Abdisamat; Alisherovich, Normuradov Nodirzhon (PT. Antis International Publisher, 2025)
Objective: To evaluate the clinical efficacy of antihistamines, antileukotrienes, and topical intranasal glucocorticosteroids in the complex therapy of exudative otitis media associated with allergic rhinitis. Methods: Patients with exudative otitis media and concurrent allergic rhinitis were treated with a combination of antihistamines, antileukotrienes, and topical intranasal glucocorticosteroids. Clinical outcomes were assessed through auditory evaluations, symptom severity scores, and quality of life measurements. Results: The therapeutic regimen demonstrated significant clinical efficacy. Patients experienced restored hearing, substantial symptom reduction, and notable improvements in overall quality of life s. Novelty: This study highlights the synergistic potential of combining antihistamines, antileukotrienes, and intranasal glucocorticosteroids, providing a comprehensive approach to managing exudative otitis media in the context of allergic rhinitis